Analyzing Student’s Problem Solving Abilities of Direct Current Electricity in STEM-based Learning - Rany Apriyani; Taufik Ramlan Ramalis; Irma Rahma Suwarma (Universitas Pendidikan Indonesia, 2019)
This research has been conducted to analyze students' problem-solving abilities in direct current electricity in STEM-based learning. The implementation of STEM in this research is to train the domain of scientific practices and engineering practices that are associated with model problems and project-based learning. The research method used was pre-experiment with the design of one group pretest-posttest. The subjects of the research consist of 27 students at the 10th grade of one of the Vocational Schools in Kabupaten Bandung Barat. The instrument of problem-solving ability in this study are four structured description questions, each of which consists of 5 questions, indicators of problem-solving ability, namely visualize the problem, describe the problem in physics description, plan the solution, execute the plan, and check and evaluate. As a result of the research, it was found that there was an increase in students' problem-solving abilities with the application of the integration model problem and project-based learning in STEM-based learning.